PHARMACEUTICALLY VALUABLE BIOACTIVE COMPOUNDS OF ALGAE - Bhattacharjee, Meenakshi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Â  Pharmaceutically valuable products from micro algae and its industrial commercialization today is still in its infancy and can be seen as a gateway to a multibillion dollar industry. Microalgae generally grow autotrophically and are ubiquitous in nature.They represent a major untapped resource of genetic potential for valuable bioactive agents and fine biochemical. This proven ability of microalgae to produce these compounds places these microorganisms in the biotechnological spotlight for applications and commercialization as in the Pharmaceutical industry. The production of microalgal metabolites, which stimulate defense mechanisms in the human body, has spurred intense study of the application of micro algal biomass and products thereof in various food preparations, pharmacological and medical products. There is therefore a huge scope for further study of the identified algal compounds and their activities in the treatment and prevention of various diseases, in addition to an ongoing search for other, as yet undetected, metabolites. Â  Key words:Algae,Pharmaceuticals, Bioactive compounds.